2019
DOI: 10.1096/fasebj.2019.33.1_supplement.586.1
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacteria is Associated with a Th1 and Th17 Immune Microenvironment in Colon Cancer Patients and Germ‐Free Mice

Abstract: Sporadic colorectal cancer (CRC) remains a global health burden with a rising incidence in younger patients (<50 years), enhancing the need to identify novel targets for diagnosis and treatment. Certain T cell subsets appear to be associated with CRC prognosis; Th1 subsets, marked by interferon gamma (IFNγ), with better prognoses, and Th17, marked by interleukin‐17 (IL‐17), with worse prognoses. Several studies have shown that Fusobacteria (Fuso), specifically Fusobacterium nucleatum (Fn), are prevalent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The co‐localization of bacteria and IL17C/CXCL1 in HS patient tunnels (Figure 4C) further cements the relationship between bacteria and HS immune activation. In other disease models, FN 21 and PN 49 have previously been shown to induce Th1/Th17 differentiation polarization in human and murine CD4 T cells, and studies from other in vivo models have shown that FN induces IL‐17A/F‐producing CD4 Th17 cell infiltration to the site of infection and that this infiltration is correlated with FN bacterial load 21,50–52 . Combined with our data, this suggests that GNAs are capable of recruiting diverse immune populations to the site of infection or colonization.…”
Section: Discussionsupporting
confidence: 81%
“…The co‐localization of bacteria and IL17C/CXCL1 in HS patient tunnels (Figure 4C) further cements the relationship between bacteria and HS immune activation. In other disease models, FN 21 and PN 49 have previously been shown to induce Th1/Th17 differentiation polarization in human and murine CD4 T cells, and studies from other in vivo models have shown that FN induces IL‐17A/F‐producing CD4 Th17 cell infiltration to the site of infection and that this infiltration is correlated with FN bacterial load 21,50–52 . Combined with our data, this suggests that GNAs are capable of recruiting diverse immune populations to the site of infection or colonization.…”
Section: Discussionsupporting
confidence: 81%